Alcântara Machado e Norman Rockwell: a arte de descrever sociedades - Rosa de Souza, Carolina Curassá [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Antônio de Alcântara Machado e Norman Rockwell são figuras representativas da produção artística das sociedades em que viveram. Machado engajou-se no modernismo brasileiro e inovou a narrativa do conto. Já Rockwell representou a cultura norte-americana por quase todo o século XX, sem utilizar, contudo, formas tão inovadoras como fez Alcântara. Esta dissertação de mestrado pretende analisar a existência de relações formais e temáticas entre os autores, ainda que haja poucas ligações artísticas, sociais ou econômicas entre eles. Valendo-se da teoria da intermidialidade e das funções da linguagem de Jakobson, busca-se estruturar um quadro comparativo e aumentar as possibilidades de leituras relativas a cultura e literatura expostas em parte da obra de Alcântara Machado e da de Norman Rockwell

Antônio de Alcântara Machado and Norman Rockwell were representative figures when we think about Brazilian and American artistic production. Machado was engaged in the Brazilian modernism and innovated the narrative structure of short-stories. Rockwell, on the other hand, represented the American culture on his canvases for almost the entire twentieth century, without using, however, the same innovative way of production as Alcântara did. This dissertation aims to analyze the existence of formal and thematic links between those artists, even with few artistic, social or economic connection between them. Drawing on the theories about Intermidiality and Jakobson’s functions of language, our intent is to structure a comparative panel and to increase the possibilities of readings related to culture and literature exhibited in the artistic production by Alcântara Machado and Normal Rockwell
Keywords: Brazilian and American art; Machado, Alcântara, 1901-1935 - Crítica e interpretação; Rockwell, Norman, 1894-1978 - Crítica e interpretação; Literatura comparada - Americana e brasileira - História e crítica; Literatura comparada - Americana e brasileira - História e crítica